Melatonin enhanced the disease resistance by regulating reactive oxygen species metabolism in postharvest jujube fruit. Issue 3 (24th January 2022) - Zhang, Lele; Yu, Youwei; Chang, Lulu; Wang, Xiaojia; Zhang, Shaoying
Abstract: Melatonin (MT), as a putative pleiotropic signal molecule, could participate in inducing postharvest disease resistance and inhibiting postharvest pathogen infection in fruit. In this study, we investigate the mechanism of induced resistance by MT treatment against Alternaria rot of jujube. The results showed that 2 and 20 μmol/L MT did not have direct antimicrobial activity, 200 μmol/L MT had little influence on antifungal activity against Alternaria alternata in vitro. MT significantly reduced the lesion area of fruit inoculated with A. alternata . MT decreased the relative electrolytic leakage, malondialdehyde content, hydrogen peroxide, and the rate of superoxide anion production, while enhanced the ascorbic acid and reduced glutathione contents. Furthermore, MT observably increased the defensive enzyme activities of superoxide dismutase, the catalase, ascorbate peroxidase, peroxidase. Accordingly, these results indicated that MT treatment increased the disease resistance of jujube fruit by regulating reactive oxygen species metabolism. Novelty impact statement: The results showed that MT treatment could inhibit the expansion of lesion diameter, reduce the decay rate of winter jujube, and reduce the accumulation of reactive oxygen species by activating the oxidase system, thus enhancing the resistance of winter Jujube fruit to Alternaria alternata infection by adjusting the ROS mechanism.